THE ROLE OF TECHNOLOGY IN ENHANCING ENGLISH LANGUAGE LEARNING: A STUDY OF DIGITAL TOOLS AND THEIR IMPACT ON STUDENT ENGAGEMENT - Handayani, Fitri (CV. Lafadz Jaya, 2024)
The rapid advancement of technology has significantly transformed the landscape of English language learning, offering learners innovative tools and platforms that enhance their engagement and comprehension. From mobile applications to online learning platforms, technology has opened new avenues for interactive and personalized language instruction. This paper explores the various ways technology has been integrated into English language learning and evaluates its impact on students’ learning outcomes, motivation, and engagement. Focusing on tools such as language learning apps, virtual classrooms, and interactive media, the study highlights the benefits of these technologies in creating an immersive and adaptive learning environment. Through a review of relevant literature and case studies, this research identifies key trends and best practices in using technology to support language acquisition. It also discusses the challenges associated with the adoption of technology, including issues of accessibility, teacher readiness, and digital literacy. The findings suggest that technology, when used effectively, can lead to improved learning outcomes by providing students with flexible, real-time feedback and fostering a more collaborative learning experience. Additionally, technology facilitates autonomous learning, allowing students to practice their language skills independently outside the classroom. However, the study also notes that successful integration of technology in language learning requires appropriate training for educators and careful consideration of learners’ individual needs.